Trends and Prospects of Financial System Development in the Context of Digitalization - LLAZO, Edlira; RYSPAEVA, Ainura; KUBICZEK, Jakub; MEHDIYEV, Vugar; KETNERS, Karlis (Theoretical and Practical Research in Economic Fields, 2024)
Due to the intensive development of technologies worldwide in the previous years, the issue of the digitalization of the financial and banking sectors is an interesting area for research, as these industries see almost immediate implementation of modern technologies. The purpose of this study is to find out the current trends in the development of the national digital market and identify its priority areas in the future. Using a combined application of multiple scientific methods, the existing financial technology toolkit was examined. As a result of the work, the positive dynamics of the share of electronic sales exceeding 20% of global volumes in 2022 was revealed, the structure of foreign direct investment in the budget of the Kyrgyz Republic was determined, where 20% is occupied by foreign investments in fintech, as well as the constant growth in the period from 2017 to 2023 of such indicators of digital economy development as the number of Internet users and social media users was noted. The Digital Code of the Kyrgyz Republic with its concept of universal codification was considered as a legislative basis for regulating digital processes. Such system-forming phenomena of the modern virtual financial system as cryptographically protected blockchain, cryptocurrencies and non-mutually exchangeable tokens were also studied. Based on the obtained data, the concept of regional leadership of the Kyrgyz Republic in creating an educational cluster was formulated, which may be of interest to the relevant ministries of the country .